1992
DOI: 10.1111/j.1476-5381.1992.tb14264.x
|View full text |Cite
|
Sign up to set email alerts
|

An ubiquitous modulating function of rabbit tracheal epithelium: degradation of tachykinins

Abstract: 1 To examine the role of epithelium in the responsiveness of tracheal smooth muscle in rabbit, we measured the contractile responses to acetylcholine (ACh), KCl, 5-hydroxytryptamine (5-HT), histamine, substance P (SP), neurokinin A (NKA), and electrical field stimulation (EFS) in intact and epitheliumdenuded preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The epithelium may also function as a metabolic barrier, reducing the amount of agonist reaching the smooth muscle layer via mechanisms such as the extraneural uptake of catecholamines (Farmer et al, 1986) or -5.0 -4.0 -3.0 -2.0 -1.0 through the effects enzymes such as neutral endopeptidase (Inoue et al, 1992) and acetylcholinesterase (Lev et al, log [ACh] 1990) that are localised in the epithelium. While the se response relationships to ACh from both correlation between epithelial loss and sensitivity to d bovine isovolumic bronchial segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epithelium may also function as a metabolic barrier, reducing the amount of agonist reaching the smooth muscle layer via mechanisms such as the extraneural uptake of catecholamines (Farmer et al, 1986) or -5.0 -4.0 -3.0 -2.0 -1.0 through the effects enzymes such as neutral endopeptidase (Inoue et al, 1992) and acetylcholinesterase (Lev et al, log [ACh] 1990) that are localised in the epithelium. While the se response relationships to ACh from both correlation between epithelial loss and sensitivity to d bovine isovolumic bronchial segments.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial damage may lead to heightened responsiveness altering permeability of the epithelial layer (Holroyde, of airways by exposure of nerve endings (Barnes, 1987(Barnes, ), 1986Mitchell et al, 1990;Munakata et al, 1989; Small depletion of a putative epithelial derived relaxant factor et al Sparrow & Mitchell, 1991). (EpDRF) (Goldie et al, 1988Stuart-Smith & Animal models have shown that factors that alter Vanhoutte, 1988, Vanhoutte, 1988), uptake or degradaepithelial permeability, such as cigarette smoke, also tion of agonists (Farmer et al, 1986, Inoue et al, 1992 alter reactivity to inhaled agonists (Hogg, 1990; however have not supported these findings. O'Byrne et al (1984) showed that while asthmatics were 20-fold more sensitive to inhaled histamine, the permeability of their airways to 99mTc-DTPA (technetium-labelled diethylenetriamine pentacetic acid) was no different than that of control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The epithelium may act also as a metabolic barrier through the degradation or uptake of bioactive molecules as they pass through the cell. For example, the epithelial layer has been shown to alter the responsiveness of rabbit tracheal strips to substance P due to the presence of neutral endopeptidase (Inoue et al 1992). In addition, the epithelium has also been demonstrated to alter the responsiveness of airways to catecholamines via extra-neural uptake mechanisms (Farmer et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…5), rather than the total amount, is critical to its function. Epithelial NEP activity is important in modulating contractile responses of airways to SP [18,19]; removal of the epithelium from 16-20 week old Japanese white rabbit tracheas enhanced contractile responses to SP; however, no difference was seen in the contractile response to SP between intact and epithelium-denuded preparations in the presence of a NEP inhibitor [19]. COLASURDO et al [18], in a preliminary report, showed that epithelial removal increased responses of tracheal rings to SP in 1 week old rabbits, but not in adults.…”
Section: Discussionmentioning
confidence: 99%